OPTIMIZATION OF THE PERSONNEL MANAGEMENT MECHANISM IN REGARD TO THE THEORY OF GENERATIONS - O. Klipkova; N. Kozmuk; O. Tsebenko (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The materials of the article focus on offering an aggregate approach to personnel management since it is the most important factor in ensuring the success of business structures. The aim of the study is to form a structural model of personnel management based on the application of the three-dimensional approach «employee — enterprise — external conditions», the theory of generations and the vector system of aspects of ethical issues in business. The study revealed a causal relationship between the behavioral characteristics of the generation and the tools of personnel management, in terms of a particular market situation, the stage of the business cycle and the level of perception of the postulates of the enterprise corporate structure. A network model of the ratio of employee and means of production based on the implementation of foreign methods of personnel management was patterned and a vector system of aspects of ethical issues in business was suggested thus ensuring the implementation of the principles of ethical behavior and universal morality.